A High‐Throughput Absolute‐Level Quantification of Protein‐Bound Amino Acids in Seeds. Issue 4 (8th November 2018) - Yobi, Abou; Angelovici, Ruthie
Abstract: In this unit, we describe a high‐throughput absolute quantification protocol for 16 protein‐bound amino acids (PBAAs) that combines a microscale protein hydrolysis step and an absolute quantification step using multiple reaction monitoring—based liquid chromatography–tandem mass spectrometry detection. The approach facilitates analysis of a few hundred samples per week by using a 96‐well‐plate extraction setup and avoiding use of additives. Importantly, the method uses only ∼3 mg of tissue per sample and includes 12 heavy‐amino‐acid internal standards to enable quantification of the absolute levels of PBAAs with high precision, accuracy, and reproducibility. The protocol described herein has been optimized for seed samples but is applicable to other plant tissues. © 2018 by John Wiley & Sons, Inc.